Three-dimensional ex vivo co-culture models of the leukaemic bone marrow niche for functional drug testing - Dhami, Sukhraj Pal S.; Kappala, Shanthi S.; Thompson, Alexander; Szegezdi, Eva (Elsevier, 2016)
Acute myeloid leukaemia (AML) is a hierarchically structured malignancy in which aberrant leukemic stem cells drive the production of leukaemic blast cell clones. AML cells strictly depend on the bone marrow microenvironment (BMM) in which they reside. Classical AML cell cultures fail to mimic the BMM and, therefore, drug discovery studies are dominated by in vivo models. However, animal models are time consuming, labour intensive, provide limited mechanistic insight, and are unsuited for high throughput studies, necessitating the development of novel AML models. The evolving ex vivo BMM mimicking culture systems aim to fill this gap, with increasing success. Here, we discuss how AML microenvironment co-culture models advance our understanding of this disease, and highlight their future potential for translational AML research.